Hamlet - Waring, James D.; Thiel, Joan E.; Myers, Emerson; Shakespeare, William, 1564-1616.; Hartke Theatre (Organization : Catholic University of America); Richard L. Coe Theater Programs Collection (Library of Congress) (Cambridge university press, London, 1971)
The Catholic University of America, the Gilbert V. Hartke Theatre presents "Hamlet," by William Shakespeare, directed by James D. Waring, settings and lighting by Mr. Waring, costumes by Joan E. Thiel, electronic sounds by Emerson Meyers, production stage manager Mary E. Holden.
Gilbert V. Hartke Theatre, January 1-17, 1971.
Title devised by Library staff.
Cast: Mark Hammer, Stephen Joyce, Anita Dangler, Peter Vogt, Philip LeStrange, Ira Lewis, Jennifer Harmon, George Vogel, Daniel Szelag, Richard Lohman, Michael Morris, Kevin Manning, Ernest Thompson, Stanley Wojewodski Jr., Jim Beard, William Hamlin, Kathleen Klein, Cheryl Faraone, Peter A. Colasante, George A. Wilson, George Vogel, Michael G. Gabel, Michael Franz, Thomas Brinson, Richard Maynes, Megan J. Bagot, Lesley Harrison, January Lohman, Mary Jane Peters, Rea Rosno, Patrick Jones, Jack Sine.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: English drama; Theater programs -- Washington (D.C.); Theater programs -- 1971.